KEKUATAN MENGIKAT RESOLUSI DEWAN KEAMANAN PBB DALAM PENYELESAIAN SENGKETA INTERNASIONAL - Oka Dananjaya, I Komang (Kertha Wicara : Journal Ilmu Hukum, 2013)
The UN Security Council has the duty to maintain international peace and security. One ofhis duties was to resolve the international dispute by way of making decisions in the form ofUN Security Council resolution. Therefore, this paper will describe the legally binding forceof the UN Security Council resolution against the countries that engage in internationaldisputes. This paper also describes the legal sanctions against offences to the SecurityCouncil resolution according to the United Nations Charter.
Keywords: UN Security Council, Resolution, Binding Force, International Disputes, Sanction